Molding sand for casting molds and its manufacturing method, casting mold, and method for improving storage stability of molding sand for casting molds

By applying specific coatings for the recycling of sand and refractory polymer surfaces and controlling the meson exchange capacity, the problems of short service life and high energy consumption of mold sand in the prior art are solved, and higher storage stability and lower environmental burden are achieved.

JP7671898B2Active Publication Date: 2025-05-02KAO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024075772
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-05-12
Filing Date
2024-05-08
Publication Date
2025-05-02
Estimated Expiration
2044-05-08

AI Technical Summary

Technical Problem

In the prior art, when using silicone gelling agent to make mold sand, heat treatment leads to high energy consumption and insufficient CO2 emissions, and insufficient liquid crosslinking leads to insufficient service life of mold sand.

Method used

By applying a specific first coating to recover sand and refractory polymer surfaces and forming a second coating containing silicate thereon, the meson exchange capacity (CEC) of the mold sand is controlled between 3 mmol(+)/kg and 40 mmol(+)/kg.

Benefits of technology

It improves the storage stability and service life of mold sand, while reducing the energy consumption and CO2 emissions required for heat treatment, and reducing environmental burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671898000001
    Figure 0007671898000001
  • Figure 0007671898000002
    Figure 0007671898000002
  • Figure 0007671898000003
    Figure 0007671898000003
Patent Text Reader

Abstract

To provide casting sand for a mold which can improve storage stability while reducing environmental loads in manufacture of casting sand for a mold.SOLUTION: Casting sand for a mold has: casting sand in which a first coating layer is arranged on the surface of one or two kinds of aggregates selected from recycled sand (A) and a fire resistant aggregate (B) containing SiO2; and a second coating layer containing silicate on the first coating layer of the casting sand, wherein a cation exchange capacity (CEC) of the casting sand is 3 mmol(+) / kg or more and 40 mmol(+) / kg or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to molding sand for foundry molds, a method for producing the same, a casting mold, and a method for improving the storage stability of molding sand for foundry molds. [Background technology]

[0002] In recent years, the importance of product design that takes people and the environment into consideration has been increasing from the perspective of the Sustainable Development Goals (SDGs), and technological development of environmentally friendly casting processes that reduce CO2 emissions and VOCs is accelerating. As an environmentally friendly casting process, for example, a wet sand inorganic binder process using refractory aggregate and an inorganic binder made of liquid water glass is known, for example, as described in Patent Document 1 (JP Patent Publication No. 2010-519042).

[0003] Patent Document 2 (JP Patent Publication No. 2021-536367) describes that by mixing recycled sand with particulate amorphous oxide containing silicon dioxide to obtain a mixture, and then heat-treating the mixture at a temperature of 400°C or higher, the pot life is improved, the surface quality of the castings is improved, and significant energy savings can be achieved. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2010-519042 [Patent Document 2] Special Publication No. 2021-536367 Summary of the Invention [Problem to be solved by the invention]

[0005] However, when molding sand for casting molds was produced by applying an inorganic binder to reclaimed sand as disclosed in the conventional Patent Documents 1 and 2, and casting was attempted, there were cases in which proper casting was not possible because liquid cross-linking by heating did not proceed sufficiently, etc. In other words, there was room for improvement in terms of extending the pot life of molding sand for casting molds. In addition, the regenerated sand obtained by the conventional method requires high-temperature treatment at 600 to 800 degrees Celsius for the regeneration process, which is insufficient in terms of reducing energy consumption and CO2 emissions.

[0006] In other words, the present invention relates to extending the pot life of molding sand for foundry molds using reclaimed sand or the like, and reducing the environmental load imposed when forming molding sand for foundry molds. [Means for solving the problem]

[0007] The present inventors have discovered that it is effective to use foundry sand for foundry molds in which a coating layer is applied to reclaimed sand or SiO2 refractory aggregate to control the cation exchange capacity (CEC) to a specific value, and have completed the present invention.

[0008] According to the present invention, Foundry sand for a mold, comprising a first coating layer disposed on a surface of one or two types of aggregate selected from recycled sand (A) and refractory aggregate (B), and a second coating layer containing silicate on the first coating layer of the foundry sand, The refractory aggregate (B) contains SiO2, The foundry sand for molds has a cation exchange capacity (CEC) of 3 mmol(+) / kg or more and 40 mmol(+) / kg or less.

[0009] The present invention also provides a casting mold made from the above molding sand for a casting mold.

[0010] Further, according to the present invention, forming a first coating layer on the surface of one or two types of aggregate selected from the recycled sand (A) and the refractory aggregate (B) to obtain molding sand having a cation exchange capacity (CEC) of 3 mmol(+) / kg or more and 40 mmol(+) / kg or less; mixing the foundry sand with a silicate to form a second coating layer containing the silicate on the first coating layer of the foundry sand; Including, The refractory aggregate (B) contains SiO2, and a method for producing molding sand for molds is provided.

[0011] Further, according to the present invention, forming a first coating layer on the surface of one or two types of aggregate selected from the recycled sand (A) and the refractory aggregate (B) to obtain molding sand having a cation exchange capacity (CEC) of 3 mmol(+) / kg or more and 40 mmol(+) / kg or less; mixing the foundry sand with a silicate to form a second coating layer containing the silicate on the first coating layer of the foundry sand; Including, The refractory aggregate (B) contains SiO2, and a method for improving the storage stability of molding sand for molds is provided. Effect of the Invention

[0012] According to the present invention, it is possible to provide molding sand for foundry molds that can reduce the environmental load during the production of the molding sand for foundry molds and can improve storage stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, embodiments of the present invention will be described. In addition, in this specification, "A to B" indicating a numerical range means a range from A to B, unless otherwise specified. In addition, the components and elements described in each embodiment can be appropriately combined as long as the effect of the invention is not impaired.

[0014] Furthermore, the "coating" and "coating layer" are not limited to being continuous, and may have some discontinuous portions.

[0015] <Molding sand> The molding sand for foundry molds of this embodiment comprises molding sand having a first coating layer disposed on the surface of one or two types of aggregate selected from recycled sand (A) and refractory aggregate (B), and a second coating layer containing silicate on the first coating layer of the molding sand, the refractory aggregate (B) containing SiO2, and the cation exchange capacity (CEC) of the molding sand is 3 mmol(+) / kg or more and 40 mmol(+) / kg or less.

[0016] That is, in the case of the present embodiment, when the molding sand for foundry molds is produced using aggregate and an inorganic binder containing silicate, the aggregate is covered with a first coating film to give the foundry sand a predetermined cation exchange capacity (CEC), and the foundry sand for foundry molds having a second coating layer containing silicate formed thereon can have improved storage stability.

[0017] Although the details of the reason for this are not clear, it is speculated as follows. (i) The surface of the reclaimed sand (A) may have residues of inorganic binders that have been used once for casting. When reclaimed sand (A) containing inorganic binder residues is mixed with an inorganic binder to produce molding sand for casting, the silicate or silicate reactant in the residues reacts with the silicate in the inorganic binder, shortening the usable time of the mixed sand. (ii) On the other hand, when molding sand for casting molds is produced by kneading refractory aggregate (B) containing SiO2 with an inorganic binder, the pot life may be shortened, as in (i), because a reaction may occur between the SiO2 component of the refractory aggregate (B) and the silicate in the inorganic binder. (iii) Therefore, by forming a first coating layer so as to cover the surface of the aggregate and making the foundry sand have a specific CEC, it is possible to suppress the reaction with the residue. As a result, even if the foundry sand is used to prepare foundry sand for molds by applying an inorganic binder, it is believed that a good pot life can be maintained and storage stability can be improved.

[0018] In addition, when the first coating layer that coats the surface of the aggregate is formed from an aluminosilicate-containing material, it can be formed at a relatively low temperature. Therefore, the roasting process at 600 to 800°C that was required for the regeneration of conventional inorganic binder processes can be omitted, and heat energy consumption and CO2 emissions can be reduced, reducing the environmental burden.

[0019] [Foundry sand] Molding sand is a type of aggregate with a first coating layer on the surface, and has a cation exchange capacity (CEC) of 3 mmol(+) / kg or more and 40 mmol(+) / kg or less. Molding sand for molds is obtained by covering the molding sand with a second coating layer, which is an inorganic binder layer.

[0020] [Cation exchange capacity] The cation exchange capacity (CEC) of the foundry sand needs to be controlled to a specific value in order to obtain good storage stability. From the viewpoint of enhancing storage stability, the cation exchange capacity (CEC) is 3 mmol(+) / kg or more, preferably 5 mmol(+) / kg or more, and more preferably 6 mmol(+) / kg or more. On the other hand, from the viewpoint of maintaining good storage stability, the cation exchange capacity (CEC) is 40 mmol(+) / kg or less, preferably 20 mmol(+) / kg or less, more preferably 10 mmol(+) / kg or less, and even more preferably 8 mmol(+) / kg or less.

[0021] The cation exchange capacity (CEC) can be controlled by combining known methods, for example, by selecting the material of the first coating layer, adjusting the content, and adjusting the firing temperature and time.

[0022] The CEC of foundry sand is determined by the ammonium acetate method shown below (Fertilizer Analysis Method (Ministry of Agriculture, Forestry and Fisheries National Institute for Agro-Environmental Sciences Method) 5.31.1). First, a small piece of absorbent cotton is placed at the bottom of the permeation tube as a support layer, and filter paper pulp made by cutting filter paper into small pieces and stirring it in hot water is packed on top of it to a thickness of about 5 mm to create a flat filtration surface. Next, a plug is placed at the bottom end of the permeation tube and several mL of 1M ammonium acetate solution is added, and 2-4 g of the analytical sample (casting sand) is weighed out and allowed to fall and settle in small amounts until the sample is filled. The plug is then removed, the device is assembled, and washing with ammonium acetate solution begins. 100 mL of 1M ammonium acetate solution is used, and the dripping speed is adjusted so that permeation is complete in 4-20 hours. After permeation is complete, the upper inside of the permeation tube is washed off with a small amount of alcohol, and the sample layer is washed with 50 mL of 80% alcohol to remove excess ammonium acetate solution. The NH4 + The analytical sample saturated with NH4 was washed with 100 mL of 10% sodium chloride solution. + The amount of ammonia nitrogen in the leachate is determined by steam distillation and alkali titration, and expressed as millimole equivalents per kg of analytical sample, which is the cation exchange capacity.

[0023] The foundry sand of this embodiment will be described in more detail below.

[0024] The molding sand of this embodiment is a particle group. From the viewpoint of improving the fluidity and further improving the filling property into the molding die, the molding sand is preferably spherical. Here, spherical molding sand refers to sand having a round shape like a ball. More specifically, from the viewpoint of improving the fluidity, mold quality, and mold strength, and from the viewpoint of ease of molding the mold, the sphericity of the molding sand is preferably 0.75 or more, more preferably 0.80 or more, and even more preferably 0.82 or more. The upper limit of the sphericity is specifically 1. In this embodiment, the sphericity of the molding sand specifically coincides with the sphericity of the refractory aggregate described below. The sphericity of molding sand is measured by analyzing the image (photograph) of a particle taken with an optical microscope or a digital scope (e.g., Keyence VH-8000) to determine the area of ​​the projected cross section of the particle and the perimeter of the cross section, and then calculating the sphericity = [area of ​​the projected cross section of the particle (mm 2The particle diameter can be calculated by dividing the circumference (mm) of a perfect circle with the same area as the particle diameter by the circumference (mm) of the projected cross section of the particle, and then averaging the values ​​obtained for any 50 particles.

[0025] (Average particle size) The average particle size of the molding sand is preferably 0.05 mm or more, more preferably 0.1 mm or more, from the viewpoints of improving mold quality and mold strength, ease of mold making, and storage stability. In addition, if the average particle size of the molding sand is equal to or more than the above lower limit, the amount of inorganic binder used in mold production can be reduced, which is also preferable in that it becomes easier to regenerate the sand into regenerated sand. From the viewpoints of improving mold quality and mold strength, and of ease of mold making, the average particle size of the molding sand is preferably 2 mm or less, more preferably 1 mm or less, and even more preferably 0.5 mm or less. In addition, if the average particle size of the molding sand is equal to or less than the above upper limit, it is also preferable in that the porosity is reduced during mold production, and the mold strength can be increased.

[0026] The average particle size of the molding sand can be measured by the following method. If the sphericity of the particle from the projected cross section is 1, the diameter (mm) is measured, whereas if the sphericity is <1, the long axis diameter (mm) and short axis diameter (mm) of the randomly oriented particles are measured to calculate (long axis diameter + short axis diameter) / 2, and the average of the values ​​obtained for any 100 particles is used as the average particle diameter (mm). The long axis diameter and short axis diameter are defined as follows: A particle is stabilized on a flat surface, and when the projected image of the particle on the flat surface is sandwiched between two parallel lines, the width of the particle at which the distance between the parallel lines is the smallest is called the short axis diameter, whereas the distance when the particle is sandwiched between two parallel lines perpendicular to the parallel lines is called the long axis diameter. The major axis diameter and minor axis diameter of a particle can be determined by taking an image (photograph) of the particle using an optical microscope or a digital scope (for example, VH-8000 model, manufactured by Keyence Corporation) and subjecting the obtained image to image analysis.

[0027] [Recycled sand (A)] The reclaimed sand (A) is an aggregate, which is a refractory material recycled from used casting molds or cores formed from a refractory aggregate and a binder, and preferably has a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate and containing one or more selected from silicates and reaction products of silicates. The reclaimed sand (A) is obtained, for example, by the manufacturing method described below.

[0028] (Fire-resistant aggregate) The material of the refractory aggregate constituting the reclaimed sand (A) may be one or more selected from the group consisting of natural sand and artificial sand. The refractory aggregate is specifically composed of a group of refractory aggregate particles.

[0029] Examples of natural sand include one or more types selected from the group consisting of silica sand, which is mainly composed of quartz, chromite sand, zircon sand, olivine sand, and alumina sand.

[0030] Examples of artificial sand include one or more types selected from the group consisting of synthetic mullite sand, SiO2-based foundry sand mainly composed of SiO2, Al2O3-based foundry sand mainly composed of Al2O3, SiO2 / Al2O3-based foundry sand, SiO2 / MgO-based foundry sand, SiO2 / Al2O3 / ZrO2-based foundry sand, SiO2 / Al2O3 / Fe2O3-based foundry sand, and slag-derived foundry sand. Here, the term "major component" refers to the component contained in the sand in the greatest amount. Artificial sand is not found in nature, but is found in sand that has been artificially prepared from metal oxide components and melted or sintered. In addition, recycled sand made from recycled refractory aggregate and recycled sand that has been regenerated can also be used.

[0031] The content of each component such as SiO2, Al2O3, and Fe2O3 in the refractory aggregate can be measured using the following X-ray fluorescence method. The refractory aggregate is adjusted to a size of approximately 0.1 μm or less using a vibration mill and heated at 1050°C for 1 hour. Then, 5 g of lithium tetraborate and 0.5 g of refractory aggregate are mixed and heated at 1200°C for 10 minutes to melt, and then cooled to prepare a glassy sample (glass bead method). The sample is subjected to X-ray fluorescence analysis using the Fundamental Parameter (FP) method using an X-ray fluorescence analyzer ZSX Primus II (manufactured by Rigaku Corporation).

[0032] The shape of the above-mentioned refractory aggregate is the same as that of the above-mentioned foundry sand, from the viewpoint of improving the fluidity of the foundry sand for molds and further improving the filling property into the molding die.

[0033] (Average particle size) The average particle size of the refractory aggregate is preferably 0.05 mm or more, more preferably 0.1 mm or more, from the viewpoints of improving the quality and strength of the mold and of ease of molding the mold. When the average particle size of the refractory aggregate is equal to or more than the above lower limit, the amount of inorganic binder used during mold production can be reduced, which is also preferable in that it makes it easier to regenerate molding sand for the mold. The average particle size of the refractory aggregate is preferably 2 mm or less, more preferably 1 mm or less, and even more preferably 0.5 mm or less, from the viewpoints of improving the mold quality and strength, and of ease of mold making. In addition, if the average particle size of the refractory aggregate is equal to or less than the above upper limit, it is also preferable in that the porosity is reduced during mold production, and the mold strength can be increased. The method for measuring the average particle size of the refractory aggregate is the same as the method for measuring the average particle size of the molding sand.

[0034] (Amorphous degree) The degree of amorphization of the refractory aggregate is preferably 20% or more, more preferably 30% or more, and even more preferably 40% or more, from the viewpoint of obtaining a smoother surface of the aggregate and thus improving mold strength, and from the viewpoint of obtaining low thermal expansion. The upper limit of the degree of amorphization of the refractory aggregate is not limited, but may be, for example, 100% or less, and may be 99% or less.

[0035] (X-ray diffraction method) The degree of amorphization of the refractory aggregate can be measured by the following X-ray diffraction method. The refractory aggregate is crushed in a mortar and pressed against an X-ray glass holder of a powder X-ray diffractometer for measurement. The powder X-ray diffractometer is a Rigaku MultiFlex (CuKα light source, tube voltage 40 kV, tube current 40 mA), and the measurement is performed in the range of 2θ = 5 to 90° with a scan interval of 0.01°, a scan speed of 2° / min, and slits DS1, SS1, and RS0.3 mm. In the range of 2θ = 10° to 50°, the X-ray intensities on the low angle side and the high angle side are connected with a straight line, the area under the straight line is taken as the background, the crystallinity is calculated using the software attached to the device, and the degree of amorphousness is calculated by subtracting it from 100. Specifically, for the area above the background, the amorphous peak (halo) and each crystalline component are separated by curve fitting, the area of ​​each is calculated, and the degree of amorphousness (%) is calculated using the following formula. Amorphous content (%) = halo area / (crystalline component area + halo area) x 100

[0036] There are various methods for controlling the degree of amorphization of refractory aggregate, but it is generally preferable to use a manufacturing method that rapidly cools the molten material. For example, there is a method in which the raw material is melted and rapidly cooled by crushing it with air, or a method in which it is treated in a flame and rapidly cooled. In either case, the cooling method may be appropriately selected at various speeds depending on the material and particle size. Another possible method is to amorphize a material that has once been crystallized by heat treatment and cooling treatment. Among these, the use of a flame fusion method, in which heating and cooling can be easily controlled, is preferable.

[0037] (Inorganic binder layer) The reclaimed sand (A) preferably has an inorganic binder layer. Specifically, the inorganic binder layer contains one or more selected from silicates and reaction products of silicates, and covers the surface of the refractory aggregate. The coating is not limited to a continuous coating, and may have discontinuous portions.

[0038] The inorganic binder layer is intended to be one in which, when foundry sand having a refractory aggregate and an inorganic binder formed on the surface of the refractory aggregate is molded into a casting mold for casting, used as a mold, and then regenerated to produce regenerated sand, the inorganic binder is present on the surface of the refractory aggregate as a residual inorganic binder. That is, the silicate and the reaction product of the silicate contained in the inorganic binder layer intend that the residual inorganic binder is present on the surface of the refractory aggregate. The silicate and the reaction product of the silicate are specifically silicate and the reaction product is the reaction product of silicate and amorphous silica, the reaction product of silicate and amorphous silica, etc., and one or more kinds are mixed.The cations constituting the salt are exemplified by monovalent cations such as sodium, potassium, lithium, and ammonium, and divalent cations such as magnesium, calcium, and zinc.

[0039] Methods for confirming that the inorganic binder layer contains silicates or reactants of silicates include, for example, a method in which the recycled sand is stirred in a hydrochloric acid solution, the components eluted are analyzed with an ICP emission spectrometer, and the concentrations of silicate ions, sodium ions, etc. are determined, a method in which the surface of the recycled sand is subjected to elemental analysis with a scanning electron microscope - energy dispersive X-ray spectroscopy (SEM-EDX) to confirm the presence of silicon, sodium, etc., or 23 Na, 29 One method is to confirm the silicate-derived structure using Si solid-state NMR.

[0040] [Fire-resistant aggregate (B)] From the viewpoint of improving mold strength by making the surface of the refractory aggregate (B) smoother, and from the viewpoint of obtaining low thermal expansion, the degree of amorphousness is preferably 20% or more, and more preferably 30% or more, and from the viewpoint of improving storage stability, the degree of amorphousness is preferably 99% or less, more preferably 80% or less, even more preferably 70% or less, and particularly preferably 60% or less.

[0041] From the viewpoint of storage stability, the SiO2 content of the refractory aggregate (B) is preferably 10% or more, more preferably 20% or more, more preferably 30% or more, and from the viewpoint of further improving mold strength, it is preferably 99% or less, more preferably 80% or less, and even more preferably 70% or less. From the viewpoint of improving storage stability, the SiO2 content of the refractory aggregate (B) is preferably 50% or less, more preferably 40% or less.

[0042] The degree of amorphization of the refractory aggregate (B) is determined by the X-ray diffraction method in the same manner as for the refractory aggregate of the recycled sand (A). In addition, the SiO2 content in the refractory aggregate (B) can be measured using the same X-ray fluorescence method as for the refractory aggregate in the recycled sand (A). In addition, the average particle size of the refractory aggregate (B) can be measured by image analysis in the same manner as for the refractory aggregate of the recycled sand (A).

[0043] [First coating layer] The first coating layer constituting the molding sand is a layer for coating the surface of one or two types of aggregate selected from the recycled sand (A) and the refractory aggregate (B), and is the outermost layer of the molding sand. The refractory aggregate (B) contains SiO2.

[0044] The first coating layer prevents the inorganic binder from acting on the aggregate (molding sand), and maintains the usable time of the molding sand for molds. In particular, by making the first coating layer from an aluminosilicate, it can be formed at a relatively low temperature, further reducing the environmental impact of heat treatment.

[0045] In this embodiment, the aluminosilicate specifically refers to either or both of the residual inorganic binder present on the surface of the refractory aggregate (B) and the refractory aggregate (B). Examples of the aluminosilicate include a reaction product of one or more selected from silicates and reaction products of silicates with an aluminate or aluminum hydroxide. In order to facilitate improving storage stability, it is preferable that the aluminosilicate contains at least one selected from among silicates and reaction products of silicates, and a reaction product of sodium aluminate or aluminum hydroxide. The form of sodium aluminate is not particularly limited, and it may be either a powder or an aqueous solution. In addition, silicate refers to a substance that has silicate in its composition, that is, a substance that contains an anion group with one or several silicon atoms at the center and electronegative ligands surrounding it in its composition. Examples of silicate include aluminosilicates and metasilicates.

[0046] The content of aluminum in the first coating layer, calculated as Al2O3, is preferably 0.1 part by mass or more, and more preferably 0.4 part by mass or more, per 100 parts by mass of the aggregate, in terms of enhancing storage stability. On the other hand, the aluminum content in the first coating layer, calculated as Al2O3, is preferably 20 parts by mass or less, and more preferably 10 parts by mass or less, per 100 parts by mass of aggregate, in order to increase the mold strength while obtaining good storage stability.

[0047] The aluminum content in the first coating layer is determined by the following method. The coefficient of elasticity can be calculated from the following formula using the analytical values ​​of the aggregates obtained by the fluorescent X-ray method and the analytical values ​​of the molding sand containing the first coating layer using these aggregates. Al2O3 of the first coating layer [parts by mass] = {Al2O3 of the molding sand [parts by mass]} - {Al2O3 of the aggregate [parts by mass]}

[0048] From the viewpoint of improving storage stability and obtaining a high-strength casting mold, the content of the first coating layer is preferably 0.02 parts by mass or more per 100 parts by mass of aggregate, preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1 part by mass or more, and especially preferably 2 parts by mass or more. From the viewpoint of achieving both storage stability and strength, the content of the first coating layer is preferably 10 parts by mass or less, and more preferably 9.5 parts by mass or less, relative to 100 parts by mass of the aggregate.

[0049] [Method of manufacturing casting sand] Next, a method for producing the foundry sand according to this embodiment will be described. The method for producing molding sand of this embodiment is a method for producing molding sand having one or two types of aggregate selected from recycled sand (A) and refractory aggregate (B), a first coating layer covering the surface of the aggregate, and a cation exchange capacity (CEC) of 3 mmol(+) / kg to 40 mmol(+) / kg. The refractory aggregate (B) contains SiO2. The molding sand is then covered with a second coating layer, and used as molding sand for a mold having an inorganic binder layer.

[0050] According to the manufacturing method of this embodiment, the cation exchange capacity (CEC) of the foundry sand obtained by forming a first coating layer on the surface of the aggregate can be controlled, thereby improving storage stability while eliminating the need for a high-temperature roasting process of the aggregate, thereby reducing thermal energy consumption and mitigating the environmental burden.

[0051] First, an example of the method for producing molding sand according to the present embodiment includes a production method including the following step (1). Step (1): A step of mixing one or two types of aggregate selected from recycled sand (A) and refractory aggregate (B) with an aluminate or aluminum hydroxide, forming a first coating layer on the surface of the aggregate, and obtaining molding sand. However, the fire-resistant aggregate (B) contains SiO2.

[0052] In step (1), the aluminate or aluminum hydroxide is mixed with the aggregate to form a first coating layer so as to cover the surface of the aggregate. In particular, it is preferable to form the first coating layer by heating to 25°C or higher and lower than 400°C. Examples of the method for forming the first coating layer by heating to 25°C or more and less than 400°C in step (1) include a method in which an aluminate is added to aggregate heated to 25°C or more and less than 400°C, or a method in which an aluminate or aluminum hydroxide is added to the aggregate and then heated to 25°C or more and less than 400°C. Among these, the latter method is preferred from the viewpoint of forming a uniform first coating layer. From the viewpoint of improving storage stability, the heating temperature is preferably 40° C. or higher and 300° C. or lower, and more preferably 70° C. or higher and 200° C. or lower.

[0053] The mixing conditions such as the stirring speed and processing time when mixing the aggregate with the aluminate or aluminum hydroxide can be appropriately determined depending on the processing amount of the mixture. This results in molding sand with a cation exchange capacity (CEC) of 3 mmol(+) / kg or more and 40 mmol(+) / kg or less. In this manner, the molding sand according to this embodiment can be obtained.

[0054] Next, the molding sand for foundry molds using the molding sand of this embodiment will be described.

[0055] <Molding sand and its manufacturing method> The foundry sand for molds has the above-mentioned foundry sand and a second coating layer containing silicate on the first coating layer of the foundry sand. That is, the foundry sand is kneaded with silicate as an inorganic binder, and the inorganic binder is adhered to the surface of the foundry sand to form the second coating layer. When the foundry sand for molds is subsequently cast into a mold, liquid bridging proceeds by heating, and a mold of the desired shape and mechanical strength can be cast.

[0056] The kneading conditions are not particularly limited, but for example, the temperature is preferably 5°C or higher, more preferably 10°C or higher, from the viewpoint of uniform kneading. On the other hand, from the viewpoint of pot life, it is preferably 40°C or lower, more preferably 35°C or lower. Furthermore, the kneading time is preferably 0.5 minutes or more, more preferably 1 minute or more, from the viewpoint of uniform kneading. On the other hand, from the viewpoint of pot life, it is preferably 10 minutes or less, more preferably 5 minutes or less. Furthermore, the kneading rotation speed is preferably 100 rpm or higher, more preferably 200 rpm or higher, from the viewpoint of uniform kneading. On the other hand, from the viewpoint of suppressing material destruction of the molding sand for the mold, it is preferably 700 rpm or lower, more preferably 500 rpm or lower.

[0057] The foundry sand for molds of this embodiment is in a wet state that does not have fluidity at room temperature. The wet state is a state in which the inorganic binder exerts adhesiveness, and for example, when heated and dried during mold casting, a solidification and hardening reaction proceeds, and a desired mold can be obtained. Specifically, if the dynamic angle of repose below cannot be measured, the material is in a "wet state."

[0058] (Method of measuring dynamic angle of repose) Put half the volume of molding sand into a cylindrical transparent plastic bottle, hold it so that its axis is horizontal, and rotate it around the horizontal axis at 60 rpm. If the molding sand does not flow inside the cylinder, or if it does flow, the slope of the layer of molding sand does not form a flat surface, and as a result, the dynamic angle of repose cannot be measured, it is in a wet state.

[0059] [Second coating layer] The second coating layer is applied to the surface of the molding sand and is obtained by using silicate as an inorganic binder. (Inorganic binder) The inorganic binder has a function of firmly binding the molding sand together so that the desired mold can be obtained when casting the mold. The inorganic binder is in a liquid state when added to the above-mentioned molding sand when it is mixed with the molding sand.

[0060] The inorganic binder contains a silicate, preferably sodium silicate, more preferably sodium silicate having a SiO2 / Na2O molar ratio of 1.0 or more and 4.0 or less, and even more preferably sodium silicate having a SiO2 / Na2O molar ratio of more than 1.1 and 4.0 or less. The inorganic binder may further contain a silicate other than the above as a main component. Specific examples of silicates other than sodium silicate include potassium silicate, lithium silicate, and ammonium silicate. In addition, in the case of a monovalent cation, the silicate of this embodiment refers to a compound represented by the general formula: xM2O·ySiO2 (x and y are any positive numerical values).

[0061] The inorganic binder may be a solution containing water glass, caustic alkali, and water. The conditions for mixing the water glass, caustic alkali, and water are not particularly limited, and a known method may be used.

[0062] The content of the inorganic binder is preferably 0.03 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.5 parts by mass or more, and even more preferably 0.9 parts by mass or more, per 100 parts by mass of aggregate. On the other hand, from the viewpoint of achieving both storage stability and strength, the content of the inorganic binder is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, per 100 parts by mass of aggregate.

[0063] (others) The molding sand for foundry molds may contain additives such as inorganic fine particles, coupling agents, moisturizing agents, moisture resistance improvers, lubricants, surfactants, and mold release agents in addition to the inorganic binder in the second coating layer.

[0064] The inorganic fine particles are not limited, and may be, for example, one or more fine particles selected from silica, silicon, zinc oxide, aluminum hydroxide, and tin oxide. Among them, silica fine particles are preferred from the viewpoint of improving the strength of the mold, and amorphous silica fine particles are more preferred from the viewpoint of large specific surface area and high reactivity with silicate. These inorganic fine particles may be used alone or in combination of two or more.

[0065] The content of the amorphous silica fine particles is preferably 0.03 part by mass or more, more preferably 0.1 part by mass or more, and even more preferably 0.5 part by mass or more, based on 100 parts by mass of the aggregate. On the other hand, from the viewpoint of achieving both storage stability and strength, the content of amorphous silica microparticles is preferably 4 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 2 parts by mass or less, and even more preferably 1 part by mass or less, per 100 parts by mass of aggregate.

[0066] The coupling agent is not limited to, but may be, for example, a silane coupling agent, a zircon coupling agent, a titanium coupling agent, or the like. Examples of the above-mentioned moisturizing agent include polyhydric alcohols, water-soluble polymers, hydrocarbons, sugars, proteins, and inorganic compounds other than those mentioned above. Examples of the moisture resistance improver include metal oxides (other than those listed above), carbonates, borates, sulfates, phosphates, and the like. Examples of the lubricant include waxes; fatty acid amides; alkylene fatty acid amides; stearic acid; stearyl alcohol; metal stearates such as lead stearate, zinc stearate, calcium stearate, and magnesium stearate; stearic acid monoglyceride; stearyl stearate; and hardened oils. Examples of the release agent include paraffin, wax, light oil, machine oil, spindle oil, insulating oil, waste oil, vegetable oil, fatty acid ester, organic acid, graphite particles, mica, vermiculite, fluorine-based release agents, and silicone-based release agents.

[0067] <Method for improving the storage stability of molding sand for molds> The method for improving the storage stability of foundry sand for molds according to the present embodiment includes a step of preparing foundry sand for molds by mixing the above-mentioned foundry sand with an inorganic binder. In other words, by using a specific foundry sand, the pot life of the foundry sand for molds can be extended and the storage stability can be improved. In detail, the foundry sand is one or two types of aggregate selected from recycled sand (A) and refractory aggregate (B) with a first coating layer disposed on the surface thereof, and the foundry sand has a cation exchange capacity (CEC) of 3 mmol(+) / kg or more and 40 mmol(+) / kg or less, and is kneaded with an inorganic binder (silicate) to adhere the inorganic binder to the surface of the foundry sand. The refractory aggregate (B) contains SiO2. The kneading method can be the same as the method for producing the foundry sand for molds described above.

[0068] The composition, manufacturing method, etc. of the foundry sand and foundry sand for molds in the method for preserving and stabilizing the foundry sand for molds are the same as those described above.

[0069] <Manufacturing method of reclaimed sand (A) / Method of reclaiming used casting sand> The method of regenerating the waste mold sand after casting can be based on known methods (for example, "Mold Making Method", 4th edition, Japan Foundry Technology Association, November 18, 1996, pp. 327-330). For example, methods such as dry grinding (mechanical abrasion), wet grinding, and roasting, as well as combinations of these processes, are known.

[0070] In the dry grinding process, a part of the inorganic binder layer residue present on the surface of the refractory aggregate can be removed. For example, the removal can be performed using a sand reclaimer in which sand is raised in the device by a high-speed air current and collided with a collision plate to perform grinding by collision and friction between sand particles, a high-speed rotary reclaimer in which sand is charged onto a rotor rotating at high speed and grinded by collision and friction between the thrown sand generated by the centrifugal force and the falling charged sand, or an agitator mill in which grinding is performed by utilizing friction between sand particles. As an example of the wet grinding treatment, there is a method using a trough grinder in which grinding is performed by friction between sand grains in a trough with rotating blades.

[0071] The roasting treatment may be, for example, a method in which sand is continuously charged into a roasting furnace such as a fluidized roasting furnace or a rotary kiln and roasted at a temperature in the range of 200 to 1000° C. It is also known that roasting at a temperature of 600 to 800° C. is used to further improve accuracy.

[0072] Any method may be used for regeneration, but the wet treatment and roasting treatment are complicated steps and involve a large energy load, so among them, the dry grinding treatment is preferred.

[0073] <Mold> The casting mold of this embodiment is formed from the molding sand for casting mold of this embodiment described above. Examples of a method for making the casting mold include a molding method using a heated molding die, and a molding method in which water vapor is passed through the heated molding die and then hot air is passed through the die.

[0074] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted.

[0075] In relation to the above-mentioned embodiment, the present invention further discloses the following molding sand for foundry molds, a method for manufacturing molding sand for foundry molds, and a method for manufacturing a casting mold. <1> Foundry sand for a mold, comprising a first coating layer disposed on a surface of one or two types of aggregate selected from recycled sand (A) and refractory aggregate (B), and a second coating layer containing silicate on the first coating layer of the foundry sand, The refractory aggregate (B) contains SiO2, The cation exchange capacity (CEC) of the foundry sand for casting molds is 3 mmol(+) / kg or more and 40 mmol(+) / kg or less, preferably 5 mmol(+) / kg or more, more preferably 6 mmol(+) / kg or more, preferably 20 mmol(+) / kg or less, more preferably 10 mmol(+) / kg or less, and even more preferably 8 mmol(+) / kg or less. <2> <1> The molding sand for foundry molds according to claim 1, Foundry sand for casting molds, wherein the content of the first coating layer is 0.02 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the aggregate. <3> <1> or <2> The molding sand for foundry molds according to claim 1, Foundry sand for molds, wherein the first coating layer contains an aluminosilicate, and the aluminosilicate is one or more selected from a mixture of one or more selected from silicates and reaction products of silicates with an aluminate, and a zeolite. <4> <3> The molding sand for foundry molds according to claim 1, Foundry sand for molds, wherein the aluminate is at least one of sodium aluminate and aluminum hydroxide. <5> <1> ~ <4> A casting mold made of any one of the molding sand for casting molds. <6> A step of forming a first coating layer on the surface of one or two types of aggregate selected from recycled sand (A) and SiO2-containing refractory aggregate (B) to obtain molding sand having a cation exchange capacity (CEC) of 3 mmol(+) / kg or more and 40 mmol(+) / kg or less; mixing the foundry sand with a silicate to form a second coating layer containing the silicate on the first coating layer of the foundry sand; Including, The method for producing molding sand for molds, wherein the refractory aggregate (B) contains SiO2. <7> <6> A method for producing molding sand for a mold according to the present invention, a method for producing molding sand for molds, wherein in the step of obtaining the molding sand, the aggregate is mixed with an aluminate or aluminum hydroxide to form the first coating layer on a surface of the aggregate. <8> <6> or <7> A method for producing molding sand for a mold according to the present invention, A method for producing molding sand for molds, in which in the step of obtaining the molding sand, the first coating layer is formed on the surface of the aggregate by heating to a temperature of 25°C or higher but lower than 400°C, preferably 40°C or higher but lower than 300°C, and more preferably 70°C or higher but lower than 200°C. <9> forming a first coating layer on the surface of one or two types of aggregate selected from the recycled sand (A) and the refractory aggregate (B) to obtain molding sand having a cation exchange capacity (CEC) of 3 mmol(+) / kg or more and 40 mmol(+) / kg or less, preferably 5 mmol(+) / kg or more, more preferably 6 mmol(+) / kg or more, preferably 20 mmol(+) / kg or less, more preferably 10 mmol(+) / kg or less, and even more preferably 8 mmol(+) / kg or less; mixing the foundry sand with a silicate to form a second coating layer containing the silicate on the first coating layer of the foundry sand; Including, The method for improving the storage stability of molding sand for casting molds, wherein the refractory aggregate (B) contains SiO2. <10> <1> ~ <4> Foundry sand for foundry molds according to any one of the preceding claims, wherein the foundry sand is a particle group. <11> <1> ~ <4> and <10> 1. The molding sand for foundry molds according to claim 1, wherein the average particle size of the refractory aggregate is preferably 0.05 mm or more, more preferably 0.1 mm or more, and is preferably 2 mm or less, more preferably 1 mm or less, and even more preferably 0.5 mm or less. <12> <1> ~ <4> , <10> and <11> The molding sand for foundry molds according to any one of the above, wherein the degree of amorphization of the refractory aggregate (B) is preferably 20% or more, more preferably 30% or more, and is preferably 99% or less, more preferably 80% or less, even more preferably 70% or less, and particularly preferably 60% or less. <12> <1> ~ <4> , <10> and <11> Foundry sand for foundry molds according to any one of the above, wherein the content of the first coating layer is, relative to 100 parts by mass of the aggregate, preferably 0.02 parts by mass or more, preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1 part by mass or more, particularly preferably 2 parts by mass or more, and is preferably 10 parts by mass or less, and more preferably 9.5 parts by mass or less. <13> <1> ~ <4> , and <10> ~ <12> 1. The molding sand for foundry molds according to claim 1, wherein the second coating layer contains a silicate, preferably a sodium silicate, and more preferably a sodium silicate having a SiO2 / Na2O molar ratio of 1.0 or more and 4.0 or less. <14> <1> ~ <4> , and <10> ~ <13> 1. The foundry sand for foundry molds according to any one of the above, wherein the content of the inorganic binder containing the silicate in the second coating layer is, relative to 100 parts by mass of the aggregate, preferably 0.03 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.5 parts by mass or more, even more preferably 0.9 parts by mass or more, and preferably 5 parts by mass or less, more preferably 4 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less. <15> <1> ~ <4> , and <10> ~ <14> 13. The molding sand for foundry molds according to claim 12, wherein the second coating film layer further contains amorphous silica fine particles. <16> <1> ~ <4> , and <10> ~ <15> 10. The molding sand for foundry molds according to claim 9, wherein the molding sand for foundry molds is in a wet state having no fluidity at room temperature. EXAMPLES

[0076] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.

[0077] (1) Material The materials used in the following examples and comparative examples will be described. [Fire-resistant aggregate] Fireproof aggregate 1: Espearl #60L (manufactured by Yamakawa Sangyo Co., Ltd., average particle size: 241 μm, degree of amorphization: 45%) Refractory aggregate (B1): Spherical fused silica (natural silica sand spheroidized by the flame fusion method, average particle size: 200 μm, degree of amorphization: 95% or more) Fireproof aggregate (B2): Naigai Cera Beads 60 #650 (manufactured by Itochu Ceratec Co., Ltd., average particle size: 200 μm, degree of amorphization: 30%)

[0078] [Inorganic fine particles] Amorphous silica particles: Denka fused silica SFP-20M (manufactured by Denka, average particle size: 0.4 μm, degree of amorphization: 99.5% or more) Calcined kaolin: Satinton W (BASF, average particle size: 0.4 μm)

[0079] [Recycled sand (A)] Reclaimed sand (A1) was prepared according to the following procedure. (i) Preparation of foundry sand containing inorganic binder 100 parts by mass of refractory aggregate 1 (Espearl #60L) was charged into the mixer as the refractory aggregate. Next, No. 2 water glass (0.90 parts by mass) and amorphous silica fine particles (0.60 parts by mass) were charged into the mixer as the inorganic binder, and the mixture was kneaded for 2 minutes to obtain casting sand for molds containing a wet inorganic binder to be used for producing reclaimed sand (A1). (ii) Preparation of the template A portion of the obtained 10 kg of molding sand for casting containing an inorganic binder was poured into the center of a truncated cone metal mold for producing a test mold, measuring 298 mm in upper diameter, 205 mm in lower diameter, and 265 mm in height, to a height of 50 mm. Then, a truncated cone metal core, measuring 280 mm in upper diameter, 200 mm in lower diameter, and 220 mm in height and heated to 180°C, was placed in the mold. The remaining molding sand for casting containing an inorganic binder was poured into the space between the metal mold and the metal core, and heated in a heating furnace at 180°C for 20 minutes to obtain a test mold. (iii) Casting 10 kg of aluminum alloy AC4C material (720℃) was poured into the obtained test mold. After pouring, it was left to stand at room temperature and cooled. (iv) Preparation of recycled sand After casting, the casting was removed from the test mold, and the test mold was crushed with a hammer or the like, and further crushed in a mini crusher (manufactured by Taiyo Machinery Co., Ltd.) until the mold became single particles, and recovered sand was obtained. (v) Preparation of recycled sand 100 kg of the recycled sand was put into a dry-type foundry sand reclamation device equipped with a fluidized bed (Hybrid Sand Master manufactured by Nippon Foundry Co., Ltd.) and batch-processed for 60 minutes at a rotor speed of 2400 rpm to obtain recycled sand (A1). Fine powder derived from the binder generated during the process was removed by a dust collector.

[0080] [Material for first coating layer] 50% sodium aluminate: Sodium aluminate #2019 (50% sodium aluminate aqueous solution manufactured by Asada Chemical Industry Co., Ltd.) Aluminum hydroxide (Al(OH)3): Aluminum hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, powder form, average particle size: 2.01 μm)

[0081] [Material for second coating layer: inorganic binder] No. 2 water glass: No. 2 sodium silicate (manufactured by Fuji Chemical Co., Ltd., Si / Na molar ratio 2.4)

[0082] (2) Preparation of molding sand and molding sand for molds The molding sands and molding sands for molds having the compositions shown in Table 1 were prepared by the following procedure.

[0083] <Example 1> 100 parts by mass of reclaimed sand (A1) was put into a mixer as a refractory aggregate. Next, 2.3 parts by mass of 50% sodium aluminate aqueous solution was put in and stirred for 2 minutes to obtain a mixture. The mixture was then heat-treated in a calciner at a roasting temperature of 80°C for 12 hours, cooled to room temperature, and then sieved through a sieve (20 mesh) to remove aggregates in the mixture, thereby obtaining a foundry sand having a first coating layer made of aluminosilicate formed on the surface of the reclaimed sand (A1). Next, the reclaimed sand (A1) with the first coating layer formed on its surface and No. 2 water glass (0.90 parts by mass) and amorphous silica fine particles (0.60 parts by mass) as inorganic binders were placed in a mixer and kneaded for 2 minutes to further coat the reclaimed sand (A1) coated with the first coating layer with a second coating layer containing the inorganic binder shown in Table 1, thereby obtaining molding sand for casting molds. Table 1 shows the composition of the molding sand and the resulting molding sand for molds.

[0084] <Examples 2 to 3> The molding sands and foundry sands for molds of Examples 2 to 3 shown in Table 1 were obtained in the same manner as in Example 1, except that the amount of 50% sodium aluminate aqueous solution added when forming the first coating layer made of aluminosilicate on the surface of the reclaimed sand (A1) was changed to the parts by mass shown in Table 1. Table 1 shows the blending compositions of the molding sands and the obtained molding sands for molds.

[0085] <Example 4> The molding sands and foundry sands for molds of Example 4 shown in Table 1 were obtained in the same manner as in Example 1, except that 0.1 parts by mass of No. 2 water glass was added when the 50% sodium aluminate aqueous solution was added to form the first coating layer made of aluminosilicate on the surface of the reclaimed sand (A1). Table 1 shows the blending compositions of the molding sands and the obtained molding sands for molds.

[0086] <Examples 5 to 8> The molding sands and foundry sands for molds of Examples 5 to 8 shown in Table 1 were obtained in the same manner as in Example 1, except that the roasting temperature for forming a first coating layer made of an aluminosilicate on the surface of the reclaimed sand (A1) was changed to the temperatures shown in Table 1. Table 1 shows the blending compositions of the molding sands and the obtained molding sands for molds.

[0087] <Example 9> Each molding sand and foundry sand for molds were obtained in the same manner as in Example 1, except that a suspension of aluminum hydroxide previously suspended in water (aluminum hydroxide:water = 1:1 mass ratio) was used instead of the 50% aqueous solution of sodium aluminate. Table 1 shows the blending compositions of the molding sand and the obtained molding sand for molds.

[0088] <Examples 10 and 12> Each molding sand and foundry sand for molds were obtained in the same manner as in Example 2, except that the recycled sand (A1) used as the refractory aggregate was changed to the refractory aggregate shown in Table 2. Table 2 shows the mix compositions of each molding sand and foundry sand for molds in Examples 10 and 12.

[0089] <Example 11> Each molding sand and each molding sand for molds were obtained in the same manner as in Example 3, except that the recycled sand (A1) as the refractory aggregate was changed to the refractory aggregate shown in Table 2. Table 2 shows the mix composition of each molding sand and each molding sand for molds in Example 11.

[0090] <Example 13> Using the foundry sand for molds obtained in Example 2, regenerated sand (A2) was obtained in the same manner as in Example 2, following the steps (ii) to (v) of the regenerated sand (A1). Using this regenerated sand (A2), foundry sand for molds was produced in the same manner as in Example 2, and the steps (ii) to (v) of the regenerated sand (A1) were repeated again to obtain regenerated sand (A3). Furthermore, using the regenerated sand (A3), the process of obtaining regenerated sand (A3) from the regenerated sand (A2) was repeated twice to obtain regenerated sand (A5). Using the reclaimed sand (A5), molding sands and molding sands for molds were obtained in the same manner as in Example 2. The results of storage stability are shown in Table 3.

[0091] <Comparative Example 1> Except for not adding 50% sodium aluminate or carrying out heat treatment, molding sand for foundry molds containing the inorganic binder of Comparative Example 1 and not containing a first coating layer made of aluminosilicate was obtained in the same manner as in Example 1. Table 1 shows the blending compositions of each molding sand and molding sand for foundry molds of Comparative Example 1.

[0092] <Comparative Examples 2 to 3> Molding sands for foundry molds of Comparative Examples 2 and 3 were obtained in the same manner as in Example 1, except that 50% sodium aluminate was not added and heat treatment was carried out at the temperatures shown in Table 1. Table 1 shows the blending compositions of each of the molding sands and molding sands for foundry molds of Comparative Examples 2 and 3.

[0093] <Comparative Example 4> 100 parts by mass of reclaimed sand (A1) was prepared as a refractory aggregate and put into a mixer. Then, 0.25 parts by mass of calcined kaolin, 0.25 parts by mass of amorphous silica fine particles, and 0.50 parts by mass of water were put in and mixed for 2 minutes. After that, the obtained mixture was heat-treated in an electric furnace at 730°C for 1 hour, then the heating of the electric furnace was stopped and the mixture was left in the electric furnace for 4 hours. Then, the mixture was taken out of the electric furnace and cooled to room temperature at room temperature, and then the mixture was passed through a sieve (20 mesh) to remove aggregates, and reclaimed sand (A1) (casting sand) with a coating layer formed was obtained. Next, the obtained molding sand, No. 2 water glass (0.90 parts by mass), and amorphous silica fine particles (0.60 parts by mass) were put into a mixer and kneaded for 2 minutes to obtain molding sand for molds of Comparative Example 4. Table 1 shows the blending compositions of each molding sand and molding sand for molds.

[0094] <Comparative Example 5> Foundry sand for foundry molds of Comparative Example 5 was obtained in the same manner as in Comparative Example 1, except that the recycled sand (A1) used as the refractory aggregate was changed to the type of refractory aggregate shown in Table 2. Table 2 shows the blending composition of the foundry sand and the foundry sand for foundry molds of Comparative Example 5.

[0095] (3) Evaluation and measurement The resulting molding sands and molding sands for molds were subjected to the following evaluations and measurements.

[0096] <Storage stability; pot life measurement> A mold test piece was prepared using the molding sand for molds immediately after kneading obtained above, and the mold strength was measured after 24 hours, and the strength was designated as S1. Meanwhile, the molding sand for molds was stored in an environment of 25°C and 55% RH, and a mold test piece was prepared under the same conditions, and the mold strength was measured after 24 hours, and the strength was designated as S2. When S1 was 100%, the time elapsed until S2 reached 80% was designated as the pot life. The preparation of the mold test pieces and the measurement of the mold strength of the mold test pieces were carried out as follows.

[0097] (Preparation of mold test pieces) A mold for 22.3 x 22.3 x 180 mm test pieces (5 pieces) was heated to 180°C. For each example, the molding sand for the mold was filled into the mold at a blow pressure of 0.45 MPa using a CSR-43 blow molding machine. The molding sand for the mold was then left to stand in the mold for 150 seconds to harden, and mold test pieces were obtained.

[0098] (Measurement of mold strength) The mold bending strength (MPa) of each of the mold test pieces obtained above was measured using a universal strength testing machine (PFG type) manufactured by George Fischer Co., Ltd., to which a PBV bending attachment had been previously attached.

[0099] [Table 1]

[0100] [Table 2]

[0101] [Table 3]

Claims

1. Foundry sand for a mold, comprising: a first coating layer disposed on a surface of one or two types of aggregate selected from recycled sand (A) and refractory aggregate (B); and a second coating layer containing silicate on the first coating layer of the foundry sand, The refractory aggregate (B) is SiO 2 Including, The foundry sand for molds has a cation exchange capacity (CEC) of 3 mmol(+) / kg or more and 40 mmol(+) / kg or less.

2. 2. The foundry sand for foundry molds according to claim 1, Foundry sand for casting molds, wherein the content of the first coating layer is 0.02 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the aggregate.

3. 3. The foundry sand for foundry molds according to claim 1 or 2, Foundry sand for molds, wherein the first coating layer contains an aluminosilicate, and the aluminosilicate is one or more selected from a mixture of one or more selected from silicates and reaction products of silicates with an aluminate, and a zeolite.

4. 4. The foundry sand for molding according to claim 3, Foundry sand for molds, wherein the aluminate is at least one of sodium aluminate and aluminum hydroxide.

5. A casting mold comprising the molding sand for casting molds according to claim 1 or 2.

6. Reclaimed sand (A) and SiO 2 forming a first coating layer on the surface of one or two types of aggregate selected from the refractory aggregate (B) containing mixing the foundry sand with a silicate to form a second coating layer containing the silicate on the first coating layer of the foundry sand; Including, The refractory aggregate (B) is SiO 2 A method for producing molding sand for a mold, comprising:

7. A method for producing the molding sand for foundry molds according to claim 6, comprising the steps of: aluminate or aluminum hydroxide is mixed with the aggregate to form the first coating layer on the surface of the aggregate in the step of obtaining the molding sand.

8. A method for producing the molding sand for foundry molds according to claim 6 or 7, comprising the steps of: A method for producing molding sand for foundry molds, comprising the step of obtaining the molding sand, heating the aggregate to a temperature of 25° C. or higher and lower than 400° C. to form the first coating layer on the surface of the aggregate.

9. forming a first coating layer on the surface of one or two aggregates selected from the recycled sand (A) and the refractory aggregate (B) to obtain foundry sand having a cation exchange capacity (CEC) of 3 mmol(+) / kg or more and 40 mmol(+) / kg or less; mixing the foundry sand with a silicate to form a second coating layer containing the silicate on the first coating layer of the foundry sand; Including, The refractory aggregate (B) is SiO 2 A method for improving the storage stability of molding sand for casting molds, comprising:

Citation Information

Patent Citations

  • Thermal regeneration of foundry sand

    JP2010519042A

  • Method for producing a particulate refractory composition for use in the production of foundry moulds and cores, corresponding uses and regenerating mixtures for heat treatment - Patents.com

    JP2021536367A

  • Porous masses or moulded bodies consisting of inorganic polymers and production thereof

    US20160068440A1

  • Particulate refractory compositions for use in the manufacture of foundry moulds and cores, methods of preparing same and corresponding uses

    WO2014019726A1

  • Coated sand, method for producing same, and method for producing casting mold using same

    WO2018097180A1